Pengaruh Pola Asuh Otoriter Terhadap Kemandirian Anak - Ellita Putri Pembayun; Mudhar Mudhar (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
This article aims to determine the effect of the authoritarian parenting style on the independence of class XII SMAN 22 Surabaya. Quantitative research using correlational design. The sample used was 100 students by taking simple random sampling. Data collection uses a measurement scale with the instrument of authoritarian and independent parenting based on the aspects of each variable. Data analysis with product moment correlation. The results show that authoritarian parenting affects independence, as evidenced by the correlation coefficient (-0.294) with a significant level of 0.003 (p <0.05). Therefore, it can be concluded that there is a negative effect of authoritarian parenting on independence. This means that low independence is a result of high authoritarian parenting. Keywords:  Parenting style;    Authoritarian Parenting; Independence